Budaya Konsumtif di Era Digital: Strategi Kapitalisme dalam Menciptakan Kebutuhan Semu - Faiza, Naila; Abdullah, Mirna Nur Alia; Mujayapura, Muhammad Retsa Rizaldi (Fakultas Ilmu Budaya, Universitas Jambi, 2025)
Consumptive culture in the digital era has become a global phenomenon triggered by modern capitalism's strategy of creating false needs. The development of digital technology, social media, and e-commerce facilitates companies to analyze consumer behavior through big data and artificial intelligence, making personalized advertising increasingly difficult to avoid. Phenomena such as FOMO (Fear of Missing Out) and influencer-based marketing reinforce the drive for overconsumption, turning wants into false needs. The impacts include financial problems, social inequality, and environmental damage due to excess waste. This research uses the literature study method to analyze digital capitalism strategies and the impact of consumptive culture. The results show the importance of digital and economic literacy to distinguish between real and false needs, as well as the need for strict regulations and a sustainable consumption movement. Public critical awareness is the key to reducing the negative impact of consumptive culture. Abstract Budaya konsumtif di era digital telah menjadi fenomena global yang dipicu oleh strategi kapitalisme modern dalam menciptakan kebutuhan semu. Perkembangan teknologi digital, media sosial, dan e-commerce memfasilitasi perusahaan untuk menganalisis perilaku konsumen melalui big data dan kecerdasan buatan, sehingga iklan yang dipersonalisasi semakin sulit dihindari. Fenomena seperti FOMO (Fear of Missing Out) dan pemasaran berbasis influencer memperkuat dorongan konsumsi berlebihan, mengubah keinginan menjadi kebutuhan palsu. Dampaknya meliputi masalah finansial, kesenjangan sosial, dan kerusakan lingkungan akibat limbah berlebih. Penelitian ini menggunakan metode studi literatur untuk menganalisis strategi kapitalisme digital dan dampak budaya konsumtif. Hasilnya menunjukkan pentingnya literasi digital dan ekonomi untuk membedakan kebutuhan nyata dan semu, serta perlunya regulasi ketat dan gerakan konsumsi berkelanjutan. Kesadaran kritis masyarakat menjadi kunci untuk mengurangi dampak negatif budaya konsumtif.